Joint ventures in Middle East oil, 1957-1975 - Stevens, Paul (Beirut : Middle East Economic Consultants, 1976)
This book examines joint venture in oil and gas industry in Middle East between 1957-1975. The book examines factors affecting the development of joint ventures and the way these joint ventures have affected the oil industry.
Includes bibliography (p. 193-197) and index.
lje 23/1/19
Loans
Keywords: Petroleum industry and trade; Oil and Gas